EKSISTENSI PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) DALAM STRUKTUR PEMERINTAHAN DAERAH - Firdaus, Firdaus (Jurnal Dinamika Hukum, 2013)
The implementation of widest autonomi be implication to the among increase local government business. Government business with transferred and afterward become task and authority of local government, not sparse to require the provisions of criminal sanctions in order to enforce value and interest of law who want to be protected by a local legal product commonly mentioned with Local Regulation. One of institutions instrumen in order to enforce Local Regulation by be contain cri-minal sanction is establishment of officer investigators specifically placed in the local and given the task of detection and investigation to the possibility of the offenses happen such as rugulated in the local regulation. The officer investigator task in the local regulation enforce, be coincide doubt Of-ficer investigator position in the local government structure, whether as local officer or central offi-cer in the local? The appear mentioned question with remember of officer investigator task and au-thority include of central government business category at the judicial area.Key words: local regulations and civil investigator